2019
DOI: 10.1017/jgc.2019.4
|View full text |Cite
|
Sign up to set email alerts
|

‘Making space’: a study into the use of mindfulness for alternative school teachers

Abstract: As teachers seek to educate and transform lives, often with limited resources and time, they can experience varying levels of stress and emotional exhaustion, particularly if effective emotion regulation strategies are not employed. The experience of teacher stress may be heightened in alternative schools that provide educational opportunities for students who present with complex needs and are ‘at-risk’ of withdrawing from the conventional school system. This case study explored the perceived outcomes of a 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
0
5
0
1
Order By: Relevance
“…Results of our review indicated that mindfulnessbased practices may be connected to the ability to regulate emotions [64,69,74,75]. Similarly, there was some evidence that mindfulness based training can be effective in prevention and management of stress by inducing emotion regulation [76].…”
Section: Interventionsmentioning
confidence: 80%
See 1 more Smart Citation
“…Results of our review indicated that mindfulnessbased practices may be connected to the ability to regulate emotions [64,69,74,75]. Similarly, there was some evidence that mindfulness based training can be effective in prevention and management of stress by inducing emotion regulation [76].…”
Section: Interventionsmentioning
confidence: 80%
“…Out [62][63][64][65][66]. In addition, mindfulness-based practices were significantly associated with lower level of job stress, anxiety, depression and job-related burnout [58,67,68].…”
Section: Interventionsmentioning
confidence: 96%
“…Alguns estudos (Fabbro et al, 2020;Flook et al, 2013;Preston & Spooner-Lane, 2019;Rodríguez & Silva, 2018) não reportaram indicadores ou ferramentas de mensuração da qualidade das modalidades de atenção plena aplicadas e a maior parte das pesquisas não mencionaram a experiência profissional dos facilitadores das estratégias, lacunas apontadas em outras pesquisas. (Emerson et al, 2017;Hwang et al, 2019).…”
Section: Discussionunclassified
“…Research-identified challenges of an SE teacher include managing complex student disability (often with poor prognosis), dealing with paraprofessionals and specialists, creating and implementing individual education programs, adaptation of (often unsuitable) curriculum and teaching materials, and an emotional expenditure that is not commensurate with teaching experience or initial teacher education (Acton & Glasgow, 2015;Billingsley & Cross, 1992;Brunsting et al, 2014). Preston and Spooner-Lane (2019) suggest that SE teachers are impacted by an absence of contextually appropriate professional development, lack of organisational support, and excessive expectation for students with complex medical, behavioural and mental health challenges to meet scholastic milestones.…”
Section: The Work Of Special Education Teachersmentioning
confidence: 99%